Radiological Assessment of Sarcopenia and Its Clinical Impact in Patients with Hepatobiliary, Pancreatic, and Gastrointestinal Diseases: A Comprehensive Review - Farook, Shameema; Soni, Saumya; Shantagiri, Arpit; Gupta, Pankaj; Sinha, Anindita; Prakash, Mahesh (Journal of Gastrointestinal and Abdominal Radiology, 2023)
Sarcopenia is defined as a syndrome characterized by progressive and generalized loss of skeletal muscle mass and strength with a risk of adverse outcomes such as physical disability, poor quality of life, and death. The diagnosis of sarcopenia is based on documentation of two of the three criteria: low muscle mass, low muscle strength, and low physical performance. Imaging-based assessment of muscle mass is preferred in both clinical and research settings. Anthropometry for the evaluation of muscle mass is prone to errors and is not recommended in the clinical setting.There is a lack of literature on the radiological assessment of sarcopenia and its association with prognosis in hepatobiliary, pancreatic, and gastrointestinal diseases. Thus, we aim to provide a review of studies that utilized radiological methods to assess sarcopenia and evaluate its impact on outcomes in patients with these diseases.
Keywords: sarcopenia; CT; MRI